(untitled) (International Journal of Engineering and Computer Science, 2014)
In cryptography, MD5 known as Message Digest 5 was developed to overcome the cryptanalytic attacks on MD4 algorithm. Most of the hash functions are based on Merkle-Damgard construction, such as MD2, MD4, MD5, and SHA1 etc are often utilized with Digital signature algorithm, Keyed Hash Message Authentication Codes, Key Derivation Functions and Random Number Generators. MD5 takes as input any message of arbitrary length and produces as output a 128 bit message digest. Though MD5 came as a modification of MD4 to overcome its weaknesses but in 2004 some serious flaws were discovered and advances were made in breaking MD5 in 2005, 2006 and 2007[1][2].This paper presents a new algorithm which is a modification of existing MD5 algorithm to overcome the various attacks possible on MD5.